Increased Nuchal Translucency as a Marker for Fetal Chromosomal Defects - Taipale, Pekka; Hiilesmaa, Vilho; Salonen, Riitta; Ylöstalo, Pekka (The New England journal of medicine, 1997)
Maternal serum screening for fetal trisomy 21 (Down's syndrome) at 15 to 16 weeks of gestation is an established practice in many countries. The biochemical basis for this approach is that in the presence of fetal trisomy 21, the average maternal serum concentrations of chorionic gonadotropin are higher than normal and those of alpha-fetoprotein and estriol are lower than normal. When the values for screening tests are set at levels that will identify approximately 60 percent of the cases of trisomy 21, about 5 percent of pregnant women will have a positive test and may then undergo chorionic-villus sampling or . . .